Level of sustained glycemic control and associated factors among patients with diabetes mellitus in Ethiopia: a hospital-based cross-sectional study - Abebe SM (Dove Medical Press, 2015)
Solomon Mekonnen Abebe,1 Yemane Berhane,2 Alemayehu Worku,3 Shitaye Alemu,1 Nebiyu Mesfin1 1University of Gondar, College of Medicine and Health Sciences, School of Medicine, Gondar, Ethiopia; 2Addis Continental Institute of Public Health, Addis Ababa, Ethiopia; 3School of Public Health, Addis Ababa University, Addis Ababa, Ethiopia Background: The level of sustained glycemic control in patients with diabetes mellitus (DM) is a major determinant of the occurrence of both acute and chronic complications. However, information about the level of glycemic control among patients in the follow-up care at the University of Gondar Referral Hospital is scanty. The study assessed the degree of glycemic control and associated factors among diabetic patients in the study area. Method: A hospital-based cross-sectional study was conducted at the University of Gondar Referral Hospital. All diabetic patients aged ≥18 years who visited the Diabetes Clinic in January and February 2013 for follow-up medical evaluation and medication participated in the study. Patients with glycosylated hemoglobin test (HbA1c) of ≥7% were classified as having a poor level of glycemic control. Propensity score was used to estimate the treatment effect. Multivariable logistic regression analysis was applied to determine the associated factors. Result: Two hundred and fifty three (64.7%) of the 391 diabetic patients included in the study had a poor level of glycemic control, as evidenced by HbA1c ≥7%. Poor glycemic control was much higher among Type 1 patients (82.9%) compared with Type 2 patients (57.5%). Being on insulin treatment (AOR =2.51; 95% CI =1.25, 5.04) and reporting poor medication adherence (AOR =3.19; 95% CI =1.76, 5.80) were found to be associated with poor glycemic control among Type 2 DM patients. High waist circumference was inversely associated with a poor level of glycemic control in Type 1 DM patients (AOR =0.05; 95% CI =0.01, 0.85). Conclusion: The proportion of diabetic patients with a poor level of glycemic control is high. We recommend a comprehensive intervention to improve the overall treatment adherence with special attention to DM patients receiving insulin. Keywords: glycemic control, HbA1c, waist circumference, diabetes mellitus, BMI